VD_FINDINFO Décision / 2023 / 30 vom 27. Januar 2023 - VD Tribunal cantonal (2023)
EXPERTISE PSYCHIATRIQUE, RÉCIDIVEINFRACTION, REJET DE LA DEMANDE | 20 CP, 139 CPP (CH), 182 CPP (CH), 189 CPP (CH), 393 al. 1 let. a CPP (CH)